Effect of Enterococcus faecalis Biofilm on Corrosion Kinetics in Titanium Grade 4 Alloys with Different Surface Treatments - Conforte, Jadison Junio [UNESP]; Sousa, Cecília Alves [UNESP]; da Silva, Ana Claudia Rodrigues [UNESP]; Ribeiro, Allan Victor; Duque, Cristiane [UNESP]; Assunção, Wirley Gonçalves [UNESP] (MDPI, 2023)
E. faecalis has been associated with bacteremia, sepsis, and bacterial endocarditis and peri-implantitis. This microorganism can remain in the alveolus even after extraction of the root remnant. This study aimed to evaluate the corrosion on different surfaces of commercially pure titanium (Ti) grade 4 (Ticp-G4) as a function of the bacterial biofilm effect of Enterococcus faecalis. A total of 57 discs were randomly divided according to their surface finish (n = 19). For microbiological analysis (n = 9), the discs were placed in 12-well plates containing E. faecalis culture and incubated at 37 °C for 7 days. The results show that for the intergroup analysis, considering the “electrolyte” factor, there was a difference between the groups. There was greater biofilm formation for the D.A.Zir group, with greater electrochemical exchange for Biofilm, and the presence of biofilm favored greater electrochemical exchange with the medium.
Keywords: biofilms; bone-integrated endo-osseous dental implantation; corrosion; titanium